2018
DOI: 10.1186/s12934-018-1001-0
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of glycerol utilization in Gluconobacter oxydans 621H for biocatalyst preparation in a low-cost way

Abstract: BackgroundWhole cells of Gluconobacter oxydans are widely used in various biocatalytic processes. Sorbitol at high concentrations is commonly used in complex media to prepare biocatalysts. Exploiting an alternative process for preparation of biocatalysts with low cost substrates is of importance for industrial applications.Results G. oxydans 621H was confirmed to have the ability to grow in mineral salts medium with glycerol, an inevitable waste generated from industry of biofuels, as the sole carbon source. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 45 publications
(44 reference statements)
0
6
0
Order By: Relevance
“…23 The best candidates to catalyse such selective oxidation would be the glycerol dehydrogenases (GlyDH) due to their natural substrate specicity. Biotechnological applications of these enzymes however are mainly limited to the whole cell production of dihydroxyacetone 24 and valuable diols through metabolic engineering. 25 Besides, this family of enzymes has also been widely applied in biosensing as the active phase of glycerol sensors.…”
Section: Introductionmentioning
confidence: 99%
“…23 The best candidates to catalyse such selective oxidation would be the glycerol dehydrogenases (GlyDH) due to their natural substrate specicity. Biotechnological applications of these enzymes however are mainly limited to the whole cell production of dihydroxyacetone 24 and valuable diols through metabolic engineering. 25 Besides, this family of enzymes has also been widely applied in biosensing as the active phase of glycerol sensors.…”
Section: Introductionmentioning
confidence: 99%
“…When cultivated using glucose as carbon source, G. oxydans converted most of the substrate into gluconate via mGDH; , gluconate was then metabolized for biomass generation through the pentose phosphate pathway or the Entner–Doudoroff pathway (Figure A). ,, When cultivated with xylose, G. oxydans oxidized some of the xylose to xylonate via mGDH, , generating electrons for energy but a limited increase in biomass. When both glucose and xylose were provided, the increase in biomass was greater than that with either substrate alone (Figure A and Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…There are at least 10 membrane-bound dehydrogenases encoded in the G. oxydans 621H genome, , each oxidizing a wide range of compounds. Utilizing the enzymatic activities of two or more membrane-bound dehydrogenases results in the combination of biosynthetic processes and may yield new applications for G. oxydans .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A series of appropriate artificial poly­(A/T) tails was reported that could enhance the mRNA abundance of the sldhAB gene coding sorbitol dehydrogenase . Several shuttle plasmids were constructed for gene overexpression via inserting the par-rep gene of cryptic plasmid from G. oxydans into pUC18 or pUC19. , Two markerless gene knockout methods were established based on 5-fluorouracil and sucrose as counter-selection reagents. These investigations contributed to the metabolic engineering of G. oxydans . However, the genetic tools for industrial strains G. oxydans , compared with Escherichia coli, Saccharomyces cerevisiae , and other model microorganisms, are relatively scarce.…”
mentioning
confidence: 99%